A method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin film and application thereof in solar cells

CN122909915APending Publication Date: 2026-10-13DALIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610781746.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

上述高温硒化过程往往会引发两方面不利影响:一方面,高温驱动下的晶粒生长速率不均,导致薄膜内部形成大量晶界;另一方面,CZTSSe吸收层表面硒元素的挥发会引入VSe深能级缺陷

Benefits of technology

(1)本发明提供的制备方法制备得到的低温后硒化处理铜锌锡硫硒薄膜,平均晶粒尺寸相较未经低温后硒化处理的薄膜明显提升。平均晶粒尺寸从未低温后硒化处理的1.45 um增大到2. 37 um,且无杂质相生成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122909915A_ABST
    Figure CN122909915A_ABST
Patent Text Reader

Abstract

The application belongs to the field of semiconductor photoelectric thin film materials and devices, and discloses a method for low-temperature post-selenization treatment of a copper-zinc-tin-sulfur-selenium thin film and application thereof in solar cells. After a copper-zinc-tin-sulfur-selenium (CZTSSe) absorption layer thin film is prepared by high-temperature selenization, the thin film is placed in an atmosphere containing selenium elements again, and is subjected to low-temperature post-selenization treatment at 240-400°C for 300-900 s. The purpose of the application is to supplement the loss of selenium elements on the surface of the thin film in the high-temperature selenization process, and to promote the migration of the grain boundary and the secondary growth of the crystal grains by using low-temperature heat driving, so as to increase the grain size. Through the above treatment, the overall crystal quality of the CZTSSe absorption layer can be effectively improved, and the photoelectric conversion efficiency of the corresponding solar cell device is increased from 5.03% to 6.36%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor optoelectronic thin film materials and devices. This invention relates to a method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films and their application in solar cells. Background Technology

[0002] Copper-zinc-tin-sulfur-selenium (Cu2ZnSn(S,Se)4, CZTSSe) is a novel inorganic compound semiconductor thin film material. Its advantages lie in its environmentally friendly constituent elements, abundant crustal reserves, tunable band gap (1.1–1.5 eV), wide spectral response range, and high light absorption coefficient (>10). 4 cm -1 It has attracted widespread attention due to its advantages such as [missing information], and has shown good application potential in the field of solar photovoltaic technology.

[0003] However, solar cells based on CZTSSe as the absorber layer still face the problem of low photoelectric conversion efficiency in practical applications. Research shows that the main reason limiting cell efficiency improvement is the excessive open-circuit voltage deficit, and the quality of the CZTSSe crystal in the absorber layer directly determines the degree of this deficit. Specifically, an ideal CZTSSe absorber layer should possess both low defect density and a dense, flat surface with grains penetrating vertically along the film thickness direction to ensure the separation and transport of photogenerated carriers and reduce their recombination rate. However, in current CZTSSe thin film fabrication processes, to promote sufficient nucleation and crystallization of the precursor film, samples are typically subjected to selenization treatment at a high temperature of 530-560 °C. This high-temperature selenization process often leads to two adverse effects: firstly, uneven grain growth rate driven by high temperature results in the formation of numerous grain boundaries within the film; secondly, the volatilization of selenium on the surface of the CZTSSe absorber layer introduces Vo. Se Deep-level defects.

[0004] Therefore, how to effectively improve the crystal quality of the CZTSSe absorber layer, especially how to compensate for the loss of selenium elements caused by high-temperature selenization, and at the same time prepare a high-quality thin film with large grain through-growth characteristics, has become a key technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, this invention provides a method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium (CZTSSe) thin films and its application in solar cells, aimed at improving the crystal quality of CZTSSe thin films. Specifically, after preparing the CZTSSe absorber layer film through high-temperature selenization, the film is placed again in a selenium-containing atmosphere and subjected to a post-selenization treatment at a low temperature of 240-400 °C for 300-900 s. The purpose of this invention is twofold: firstly, to compensate for the selenium loss on the film surface during high-temperature selenization; and secondly, to utilize low-temperature thermal drive to promote grain boundary migration and secondary grain growth, thereby increasing grain size. Through this treatment, the overall crystal quality of the CZTSSe absorber layer can be effectively improved, thereby increasing the photoelectric conversion efficiency of the corresponding solar cell device from 5.03% to 6.36%.

[0006] The above-mentioned objective of this invention is achieved through the following technical solution: A method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films specifically includes the following steps: (1) Preparation of copper-zinc-tin-sulfur (CZTS) precursor thin film: copper source, zinc source, tin source and sulfur source are mixed in a certain molar ratio and stirred with a magnetic stirrer until completely dissolved to obtain CZTS precursor solution; then, in a glove box filled with argon, the prepared CZTS precursor solution is uniformly spin-coated onto a molybdenum-plated glass substrate; after spin-coating, the obtained film is immediately baked on a heating stage to obtain CZTS precursor thin film.

[0007] (2) High-temperature selenization to prepare CZTSSe absorber film: The CZTS precursor film prepared in step (1) is placed in a selenium atmosphere and selenized at high temperature to obtain CZTSSe absorber film.

[0008] (3) Low-temperature selenization treatment of CZTSSe absorber film: The CZTSSe absorber film obtained in step (2) is placed in a selenium-containing atmosphere and subjected to low-temperature selenization treatment in the temperature range of 240-400 °C to obtain a low-temperature selenization treatment copper-zinc-tin-sulfur-selenium film.

[0009] Furthermore, in step (1), the copper source is cuprous chloride, the zinc source is zinc chloride, the tin source is stannous chloride dihydrate, and the sulfur source is thiourea.

[0010] Furthermore, in step (1), the molar ratio of copper source, zinc source, tin source and sulfur source in the CZTS precursor solution is 5.72: 4.35: 3.65: 20.53. The preferred molar ratio is 5.72: 4.35: 3.65: 20.53.

[0011] Furthermore, in step (2), the high-temperature selenization temperature is 530-550 °C and the holding time is 600-1200 s.

[0012] Furthermore, in step (3), it is preferred to perform low-temperature selenization treatment at 240 °C, 260 °C, 280 °C, 320 °C, 350 °C or 400 °C.

[0013] Further, in step (3), the specific operation of low-temperature post-selenization is as follows: the CZTSSe absorber film is placed in a graphite box containing 50-150 mg of selenium particles, and low-temperature post-selenization is carried out in a rapid annealing furnace under nitrogen protection; the specific temperature is set as follows: first, the temperature is raised to 200 °C at a heating rate of 1.8 °C / s and held for 100 s; then, the temperature is rapidly raised to 240-400 °C at a heating rate of 6.6 °C / s and held for 300-900 s; finally, the temperature is naturally cooled to room temperature to complete the entire low-temperature post-selenization process.

[0014] Furthermore, in step (3), a low-temperature selenization treatment is performed in the temperature range of 240-400 °C to replenish the selenium element lost by the film surface during the high-temperature selenization process, and to promote grain boundary migration and secondary grain growth, thereby improving the crystal quality of the CZTSSe absorber layer.

[0015] This invention also claims protection for the application of the low-temperature post-selenization copper-zinc-tin-sulfur-selenium thin film prepared by the above method in the preparation of CZTSSe thin-film solar cells, specifically, the low-temperature post-selenization copper-zinc-tin-sulfur-selenium thin film as an absorber layer.

[0016] This invention also claims protection for the aforementioned CZTSSe thin-film solar cell, the structure of which is SLG / Mo / CZTSSe / CdS / i-ZnO / ITO / Ag.

[0017] The preparation method of CZTSSe thin-film solar cell includes: low-temperature selenization treatment of copper-zinc-tin-sulfur-selenium thin film as absorber layer, deposition of 50 nm thick CdS buffer layer on the surface of absorber layer by chemical water bath method, followed by deposition of 50 nm thick i-ZnO and 250 nm thick ITO by magnetron sputtering, and finally deposition of Ag electrode by thermal evaporation method to complete the preparation of cell.

[0018] Furthermore, the chemical water bath deposition temperature is 60 °C and the time is 15 min.

[0019] Furthermore, the base vacuum of the magnetron sputtering is 5. 10 -4For i-ZnO deposition, the RF sputtering power was 75 W, the working pressure was 1.2 Pa, the substrate temperature was room temperature, and the sputtering time was 370 s. For ITO deposition, the DC sputtering power was 65 W, the working pressure was 0.37 Pa, the substrate temperature was room temperature, and the sputtering time was 230 s.

[0020] The advantages of this invention compared to the prior art are: (1) The copper-zinc-tin-sulfur-selenium thin film prepared by the preparation method provided by the present invention has a significantly improved average grain size compared with the film without low-temperature selenization treatment. The average grain size increased from 1.45 μm to 2.37 μm without low-temperature selenization treatment, and no impurity phase was generated.

[0021] (2) The preparation method provided by the present invention is used to perform low-temperature selenization treatment on copper-zinc-tin-sulfur-selenium thin films, which can optimize the grain growth process and obtain large grain absorption layer films. The efficiency of CZTSSe thin film solar cells prepared thereby is increased from 5.03% to 6.36%. Attached Figure Description

[0022] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0023] Figure 1 The images show the XRD patterns of the CZTSSe films prepared in Examples 1-6 after low-temperature post-selenization treatment and the CZTSSe film prepared in Comparative Example 1 without post-selenization.

[0024] Figure 2 These are SEM surface morphology comparison images of the CZTSSe films prepared in Examples 1-6 after low-temperature post-selenization treatment and the CZTSSe film prepared in Comparative Example 1 without post-selenization. Figure (A) shows the SEM surface morphology of the CZTSSe film in Comparative Example 1 without post-selenization; Figure (B) shows the SEM surface morphology of the CZTSSe film in Example 1 after low-temperature post-selenization; Figure (C) shows the SEM surface morphology of the CZTSSe film in Example 2 after low-temperature post-selenization; Figure (D) shows the SEM surface morphology of the CZTSSe film in Example 3 after low-temperature post-selenization; Figure (E) shows the SEM surface morphology of the CZTSSe film in Example 4 after low-temperature post-selenization; Figure (F) shows the SEM surface morphology of the CZTSSe film in Example 5 after low-temperature post-selenization; Figure (G) shows the SEM surface morphology of the CZTSSe film in Example 6 after low-temperature post-selenization; and Figure (H) is a statistical chart of the average grain size of the CZTSSe films in Comparative Example 1 and Examples 1-6. In the (H) figure, the horizontal axis from a to g represents: Comparative Example 1, Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6.

[0025] Figure 3 These are comparative SEM cross-sectional morphologies of CZTSSe thin films in Comparative Example 1 and Example 4. Figure (a) shows the SEM cross-sectional morphology of the CZTSSe thin film in Comparative Example 1; Figure (b) shows the SEM cross-sectional morphology of the CZTSSe thin film in Example 4.

[0026] Figure 4 Figure 1 shows the application examples and measurement results. Figure (a) is a schematic diagram of the CZTSSe thin-film solar cell in Application Example 1; Figure (b) shows the JV curves of the cells prepared in Application Example 1 using the CZTSSe thin films of Comparative Example 1 and Example 4 as the absorber layer, respectively; Figure (c) shows the open-circuit voltage (V) of the cells prepared in Application Example 1 using the CZTSSe thin films of Comparative Example 1 and Example 4 as the absorber layer, respectively. OC Figure (d) shows the box plot of the cells prepared in Application Example 1 using the CZTSSe thin film of Comparative Example 1 and Example 4 as the absorber layer, respectively. SC Figure (e) is a box plot of the fill factor (FF) of the batteries prepared in Application Example 1 using the CZTSSe films of Comparative Example 1 and Example 4 as the absorber layer, respectively; Figure (f) is a box plot of the power conversion efficiency (PCE) of the batteries prepared in Application Example 1 using the CZTSSe films of Comparative Example 1 and Example 4 as the absorber layer, respectively. Wherein, Control represents the battery prepared using the CZTSSe film of Comparative Example 1 without post-selenization treatment as the absorber layer, and Se-treated represents the battery prepared using the CZTSSe film of Example 4 with low-temperature post-selenization treatment as the absorber layer; and Figure 4 Data for each of the six batteries is presented in (c)-(f). Detailed Implementation

[0027] The present invention is described in detail below through specific embodiments, but this does not limit the scope of protection of the present invention. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can all be obtained commercially.

[0028] This invention involves placing a CZTSSe absorber layer film, prepared by high-temperature selenization, in a selenium-containing atmosphere and performing a low-temperature post-selenization treatment at 240-400°C for 300 seconds. When the post-selenization temperature is within the range of 240-320°C, this treatment can replenish the selenium element lost from the film surface during the high-temperature selenization process, promote secondary grain growth and grain boundary migration, significantly increase grain size, and obtain a high-quality CZTSSe film with a large grain through-hole structure. The solar cell structure prepared using this film as the absorber layer is SLG / Mo / CZTSSe / CdS / i-ZnO / ITO / Ag. This invention has a simple process, good controllability, and can effectively improve the crystal quality of the absorber layer, thereby improving the photoelectric conversion efficiency of the cell.

[0029] Example 1 A method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films, the specific steps of which are as follows: (1) Preparation of CZTS precursor solution: A 20×20 mm Mo-plated sodium-calcium glass (SLG) slide was selected as the substrate. First, 0.5659 g of CuCl and 0.8236 g of SnCl2·2H2O were dissolved in 5 mL of DMSO and stirred with a magnetic stirrer for 12 h. Then, 0.5929 g of ZnCl2 was added to the above solution and stirred for 1.5 h. Finally, 1.5602 g of CH4N2S was added to the above solution and stirred for 1 h until the solution was completely dissolved, thus obtaining the CZTS precursor solution. Then, in an argon-filled glove box, the prepared CZTS precursor solution was uniformly spin-coated onto the SLG substrate with a Mo back electrode. The spin-coating process was 800 rpm for 10 s and then 3000 rpm for 25 s. After spin-coating, the obtained film was immediately baked on a heating stage at 430 °C for 2.5 min. Repeat the spin coating and baking process 8 times to obtain the CZTS precursor film.

[0030] (2) High-temperature selenization to prepare CZTSSe absorber film: Next, the CZTS precursor film obtained in step (1) is placed in a graphite box containing 150 mg selenium particles and annealed in a rapid heating furnace at 550 °C for 900 s to obtain the CZTSSe film.

[0031] (3) Low-temperature post-selenization treatment of CZTSSe absorber film: The CZTSSe film prepared in step (2) above was placed in a graphite box containing 150 mg of selenium particles and subjected to low-temperature post-selenization treatment in a rapid annealing furnace under nitrogen protection. The specific temperature curve was as follows: first, the temperature was raised to 200 °C at a heating rate of 1.8 °C / s and held for 100 s; then, the temperature was rapidly raised to the target temperature (240 °C) at a heating rate of 6.6 °C / s and held for 300 s; finally, the temperature was naturally cooled to room temperature to obtain the CZTSSe film after low-temperature post-selenization treatment.

[0032] Example 2 The target temperature in step (3) is 260 °C, and the rest is the same as in Example 1.

[0033] Example 3 The target temperature in step (3) is 280 °C, and the rest is the same as in Example 1.

[0034] Example 4 The target temperature in step (3) is 320 °C, and the rest is the same as in Example 1.

[0035] Example 5 The target temperature in step (3) is 350 °C, and the rest is the same as in Example 1.

[0036] Example 6 The target temperature in step (3) is 400 °C, and the rest is the same as in Example 1.

[0037] Comparative Example 1 The method for post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films includes the following specific steps: (1) Preparation of CZTS precursor solution: A 20×20 mm Mo-plated sodium-calcium glass (SLG) slide was selected as the substrate. First, 0.5659 g of CuCl and 0.8236 g of SnCl2·2H2O were dissolved in 5 mL of DMSO and stirred with a magnetic stirrer for 12 h. Then, 0.5929 g of ZnCl2 was added to the above solution and stirred for 1.5 h. Finally, 1.5602 g of CH4N2S was added to the above solution and stirred for 1 h until the solution was completely dissolved, thus obtaining the CZTS precursor solution. Then, in an argon-filled glove box, the prepared CZTS precursor solution was uniformly spin-coated onto the SLG substrate with a Mo back electrode. The spin-coating process was 800 rpm for 10 s and then 3000 rpm for 25 s. After spin-coating, the obtained film was immediately baked on a heating stage at 430 °C for 2.5 min. Repeat the spin coating and baking process 8 times to obtain the CZTS precursor film.

[0038] (2) High-temperature selenization to prepare CZTSSe absorber film: Next, the CZTS precursor film obtained in step (1) is placed in a graphite box containing 150 mg selenium particles and annealed in a rapid heating furnace at 550 °C for 900 s to obtain the CZTSSe film.

[0039] Depend on Figure 1 XRD analysis revealed that all prepared CZTSSe films exhibited a zinc chrystanite structure. Low-temperature selenization treatment within the range of 240–320 °C yielded a single-phase CZTSSe film, while a SnS impurity phase began to appear at 350 °C. Figure 2 SEM surface morphology images showed that, compared with the untreated film, the average grain size of the film significantly increased after low-temperature selenization. However, when the temperature rose to 350 °C, impurity phases began to appear on the sample surface, which is consistent with the XRD test results. Therefore, combined XRD and SEM analyses indicate that the crystallinity of the CZTSSe films prepared at low-temperature selenization temperatures of 240–320 °C was improved, and no impurity phases were generated. Figure 3 SEM cross-sectional images of CZTSSe films treated with selenization at 320 °C and post-selenization at low temperature show that this condition can yield high-quality CZTSSe films with large grain penetration.

[0040] Application Example 1 Using the CZTSSe thin film prepared in Example 4 after low-temperature selenization treatment and the CZTSSe thin film prepared in Comparative Example 1 without selenization treatment as absorber layers, solar cells were fabricated. The cell fabricated with the CZTSSe thin film of Comparative Example 1 is designated as Control, and the cell fabricated with the CZTSSe thin film of Example 4 is designated as Se-treated. The specific steps are as follows: (1) Deposition of CdS buffer layer using chemical bath method. 0.0768 g CdSO4·8 / 3H2O was dissolved in a beaker containing 200 mL deionized water and stirred for 7.5 min until completely dissolved. Then 12.5 mL concentrated ammonia was added and stirred for 5 min. Then a sample holder containing a clean CZTSSe film (the CZTSSe film prepared in Comparative Example 1 and Example 4) was placed in the beaker, sealed, and stirred for 10 min. Then 0.11 g CH4N2S was added and stirred for 3 min. Then the beaker was placed in a 60 °C water bath for 15 min. After the reaction was completed, the sample was removed and dried in a 40 °C oven for 60 s to obtain the SLG / Mo / CZTSSe / CdS multilayer film structure.

[0041] (2) Next, i-ZnO and ITO window layers were prepared by radio frequency magnetron sputtering and DC magnetron sputtering, respectively. First, under a vacuum degree ≤5×10-4 High-purity argon gas was introduced into the cavity of the Pa sputtering chamber. The RF sputtering power was controlled at 75 W, the working pressure at 1.2 Pa, the substrate temperature at room temperature, and the sputtering time at 370 s to deposit an i-ZnO layer with a thickness of about 50 nm. Subsequently, the DC sputtering power was controlled at 65 W, the working pressure at 0.37 Pa, the substrate temperature at room temperature, and the sputtering time at 230 s to deposit an ITO layer with a thickness of about 250 nm, thus obtaining a SLG / Mo / CZTSSe / CdS / i-ZnO / ITO multilayer thin film structure.

[0042] (3) Finally, the Ag top electrode was prepared by vacuum thermal evaporation. The sample after magnetron sputtering was placed in a vacuum evaporation chamber, and high-purity Ag particles were used as the evaporation source. The evaporation was carried out under a vacuum degree ≤ 5 × 10⁻⁶. -4 Under the condition of Pa, the evaporation source current is controlled at 80-100 A, and an Ag top electrode with a thickness of about 200 nm is deposited through a mask to complete the fabrication of the SLG / Mo / CZTSSe / CdS / i-ZnO / ITO / Ag structure device.

[0043] The performance of the prepared battery was measured, and the results are shown in the figure. Figure 4 .

[0044] Depend on Figure 4 (b) shows that the battery performance test results in Comparative Example 1, prepared using the CZTSSe thin film without post-selenization treatment, have an open-circuit voltage of 381 mV and a short-circuit current density of 29.72 mA / cm². -2 The fill factor is 44.33%, and the photoelectric conversion efficiency is 5.03%. The battery prepared in Example 4 using a CZTSSe thin film treated with selenization at 320 °C has an open-circuit voltage of 388 mV and a short-circuit current density of 33.32 mA / cm². -2 The fill factor was 49.11% and the photoelectric conversion efficiency was 6.36%. That is, the photoelectric conversion efficiency of the solar cell made by using the CZTSSe thin film as the absorber layer after selenization treatment at 320 °C was improved by 1.33% compared with the untreated sample. Figure 4 The statistical results of the battery performance in (c)-(f) all show that selenization treatment at 320 °C can significantly improve the photoelectric conversion efficiency of CZTSSe thin film solar cells.

[0045] The embodiments described above are merely preferred embodiments of the present invention, and not all feasible embodiments of the present invention. Any obvious modifications made by those skilled in the art without departing from the principles and spirit of the present invention should be considered to be included within the scope of protection of the claims of the present invention.

Claims

1. A method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films, characterized in that, Specifically, the following steps are included: (1) Preparation of copper-zinc-tin-sulfur precursor thin film: copper source, zinc source, tin source and sulfur source are mixed in a certain molar ratio and stirred with a magnetic stirrer until completely dissolved to obtain CZTS precursor solution; Then, in an argon-filled glove box, the prepared CZTS precursor solution was uniformly spin-coated onto a molybdenum-plated glass substrate; after spin-coating, the resulting film was immediately baked on a heating stage to obtain the CZTS precursor film. (2) High-temperature selenization to prepare copper-zinc-tin-sulfur-selenium absorber film: The CZTS precursor film prepared in step (1) is placed in a selenium atmosphere and selenized at high temperature to obtain CZTSSe absorber film. (3) Low-temperature selenization treatment of CZTSSe absorber film: The CZTSSe absorber film obtained in step (2) is placed in a selenium-containing atmosphere and subjected to low-temperature selenization treatment in the temperature range of 240-400 °C to obtain a low-temperature selenization treatment CZTSSe film.

2. The method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films as described in claim 1, characterized in that, In step (1), the copper source is cuprous chloride, the zinc source is zinc chloride, the tin source is stannous chloride dihydrate, and the sulfur source is thiourea.

3. The method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films as described in claim 1, characterized in that, In step (1), the molar ratio of copper source, zinc source, tin source and sulfur source in the CZTS precursor solution is 5.72: 4.35: 3.65: 20.

53.

4. The method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films as described in claim 1, characterized in that, In step (2), the high-temperature selenization temperature is 530-550 °C and the holding time is 600-1200 s.

5. The method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films as described in claim 1, characterized in that, In step (3), a low-temperature selenization treatment is performed at 240 °C, 260 °C, 280 °C, 320 °C, 350 °C or 400 °C.

6. The method for low-temperature post-selenization treatment of copper-zinc-tin-sulfur-selenium thin films as described in claim 1, characterized in that, In step (3), the specific operation of low-temperature post-selenization is as follows: the CZTSSe absorber film is placed in a graphite box containing 50-150 mg of selenium particles, and low-temperature post-selenization is carried out in a rapid annealing furnace under nitrogen protection; the specific temperature is set as follows: first, the temperature is raised to 200 °C at a heating rate of 1.8 °C / s and held for 100 s; then, the temperature is rapidly raised to 240-400 °C at a heating rate of 6.6 °C / s and held for 300-900 s; finally, the temperature is naturally cooled to room temperature to complete the entire low-temperature post-selenization process.

7. The application of the low-temperature post-selenization treated copper-zinc-tin-sulfur-selenium thin film prepared by the method according to any one of claims 1-6 in the preparation of CZTSSe thin-film solar cells.

8. The application as described in claim 7, characterized in that, A copper-zinc-tin-sulfur-selenium thin film was used as an absorber layer after low-temperature selenization treatment.

9. A CZTSSe thin-film solar cell, characterized in that, The low-temperature post-selenization copper-zinc-tin-sulfur-selenium thin film prepared by the method according to any one of claims 1-6 is used as the absorber layer; the structure of the CZTSSe thin film solar cell is SLG / Mo / CZTSSe / CdS / i-ZnO / ITO / Ag.

10. The method for preparing CZTSSe thin-film solar cells as described in claim 9, wherein a copper-zinc-tin-sulfur-selenium thin film is used as an absorber layer after low-temperature selenization treatment, a CdS buffer layer is deposited on the surface of the absorber layer using a chemical bath method, followed by i-ZnO and ITO being deposited sequentially by magnetron sputtering, and finally an Ag electrode is deposited using a thermal evaporation method to complete the preparation of the cell.